Jiuding capital : private equity form with Chinese characteristics - Meng, Fei, (SAGE knowledge. Cases., 2016)
On December 9th, 2010, 'The 10th China Venture Capital & Private Equity Annual Forum' organized by Zero2IPO was held in Hyatt on the Bund in Shanghai, attracting the eyeballs of thousands of professionals in the industry. Since 2008 when the dominance of foreign private equity funds (PEs) in the Chinese market was weakened, local PEs are rising rapidly and becoming a new force of the industry. The most eyeball-catching one is the winner of four big prizes at the forum - Jiuding Capital.